(E)-N′-(5-Bromo-2-hydroxybenzylidene)-3-methylbenzohydrazide - Hai-Chang Guo; Shi-Yong Liu; Xiao-Ling Wang (Acta Crystallographica Section E, 2011)
In the title molecule, C15H13BrN2O2, an intramolecular O—H...N hydrogen bond influences the molecular conformation; the two benzene rings form a dihedral angle of 13.6 (3)°. In the crystal, intermolecular N—H...O hydrogen bonds link the molecules into chains along the a axis and weak intermolecular C—H...O hydrogen bonds further link these chains into layers parallel to the ac plane.